Synthesis of some aromatic chloro acetamide from aromatic amines compounds, and (Z) -5- (4-dimctlryl amino benzelidcn) -2- amino - thiazalidin -4- one derivatives - M. Daher AI-.libory, Abed; ldrees, Halla (Tikrit Journal of Pharmaceutical Sciences, 2023)
Arylamine compounds were reacted with chloro acetyl chloride to convert the amino group to amide (compounds -1, 4, 7) these later compounds allowed to reacts with arylamino to produce the new (compounds -3, 6, 9), and the above compounds allowed to react with potassium thiocynate to prepare the new compounds which containing thiazolidinone (five membered rings) the (compounds -2, 5, 8), the later compounds allowed to react with aryl aldehydes to prepare the (compounds -10, 11, 12). The prepared compounds were identified using melting point apparatus, Infrared spectroscopy, and (H1-NMR).